1988
DOI: 10.2527/jas1988.663699x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fiber on Young Adult Genetically Lean, Obese and Contemporary Pigs: Body Weight, Carcass Measurements, Organ Weights and Digesta Content

Abstract: Twenty-one genetically lean, obese or contemporary barrows (6 mo old; seven of each genotype) were assigned to individual tether stalls and fed a control diet (low-fiber) or a diet containing 80% alfalfa meal (high-fiber) at 1.50% of initial body weight for 71 d (1.75% for d 1 to 4). Backfat thickness was recorded ultrasonically at 2-wk intervals, and body weight was recorded at the beginning and end of the 10-wk experiment. Pigs were slaughtered after a 24-h fast, and carcass weight, length and backfat thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
4
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 0 publications
8
70
4
4
Order By: Relevance
“…The lack of impact on body weight could be explained by an increased weight of digestive tract in sows fed the HF diet during gestation. Such an impact on the digestive tract has been shown in growing pigs (Pond et al, 1988;Jørgensen et al, 1996).…”
Section: --mentioning
confidence: 82%
“…The lack of impact on body weight could be explained by an increased weight of digestive tract in sows fed the HF diet during gestation. Such an impact on the digestive tract has been shown in growing pigs (Pond et al, 1988;Jørgensen et al, 1996).…”
Section: --mentioning
confidence: 82%
“…The digestibility coefficients (Table 3) for sticky coffee hulls were lower than those obtained by Poveda-Parra et al (2008) and Ferreira et al (1997) for DE (2,498 and 2,843 kcal/kg, respectively) and DCCP (45.7 and 65.5%, respectively). Similarly, the values found are lower than those observed by Oliveira et al (2002) and Ferreira et al (1997) for DDM (65.6 and 61.0%, respectively) and ME (2,684 and 2,694kcal/kg, respectively).…”
Section: Resultsmentioning
confidence: 38%
“…There may be decrease in dry matter digestibility result of the partial substitution of a highly digestible carbohydrate source (corn starch) by another less digestible source, rich in non-starch polysaccharides (NSP), with lower fermentation or through an increase in intestinal transit, leading to a reduction in the fermentation of structural carbohydrates (Gomes et al, 2007). The digestible coefficients (DC) and metabolizable coefficients (MC) of gross energy were not influenced (P>0.05) by the levels of substitution, but for Pond et al (1988) found a reduction in the digestibility of energy in diets with high fiber inclusion. According to Kempen (2001) for each 1% of fiber added to the diet of pigs, energy digestibility also falls by at least 1%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations